2020
DOI: 10.3390/microorganisms8030455
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Cinnamaldehyde on Quorum Sensing and Biofilm Susceptibility to Antibiotics in Pseudomonas aeruginosa

Abstract: Quorum sensing (QS) plays an important role during infection for the opportunistic human pathogen Pseudomonas aeruginosa. Quorum sensing inhibition (QSI) can disrupt this initial event of infection without killing bacterial cells, and thus QS inhibitors have been suggested as novel approaches for anti-infective therapy. Cinnamaldehyde (CAD) is a P. aeruginosa biofilm inhibitor and disperser of preformed biofilms. In this study, the combined use of CAD and colistin (COL) revealed a synergistic activity, but thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…In the era of antimicrobial resistance, antivirulence strategies have been endorsed as an attractive approach to control bacterial infections. Instead of imposing a selective pressure on bacterial growth, many virulence-suppressing compounds can attenuate the production of virulence factors and QS-based bacterial communication, disarming the pathogens and leading to reduced pathogenicity [ 10 , 12 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the era of antimicrobial resistance, antivirulence strategies have been endorsed as an attractive approach to control bacterial infections. Instead of imposing a selective pressure on bacterial growth, many virulence-suppressing compounds can attenuate the production of virulence factors and QS-based bacterial communication, disarming the pathogens and leading to reduced pathogenicity [ 10 , 12 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several synthetic and natural compounds have shown efficacy as antibiofilm and anti-QS agents [ 11 , 12 ]. Among them, Chitosan has recently attracted much interest as evidence is accumulating that the biopolymer extracted from different sources may interfere with QS and biofilm formation of bacterial pathogens [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently natural plant extracts have become of great interest to researchers due to their volatile nature, aroma, antioxidant and antimicrobial properties [ 6 , 7 ]. Further, plant disease management with plant essential oils has been recognized as one of the best approaches [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that combined treatment downregulated QS system-associated gene expression more effectively. Furthermore, Topa et al proposed a combination therapy of cinnamaldehyde with tobramycin as an alternative to mitigate P. aeruginosa infections ( 42 ). Tobramycin showed strong QS inhibitory activity when combined with cinnamaldehyde.…”
Section: Discussionmentioning
confidence: 99%